2011
DOI: 10.1002/ijc.25452
|View full text |Cite
|
Sign up to set email alerts
|

miR‐137 targets Cdc42 expression, induces cell cycle G1 arrest and inhibits invasion in colorectal cancer cells

Abstract: miRNAs have emerged as post-transcriptional regulators that are critically involved in the pathogenesis of a number of human cancers. Cdc42, one of the best characterized members of the Rho GTPase family, is found to be up-regulated in several types of human tumors and has been implicated in cancer initiation and progression. In the present study, we have identified miR-137 as a potential regulator of Cdc42 expression. A bioinformatics search revealed a putative target-site for miR-137 within the Cdc42 3 0 UTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 32 publications
(37 reference statements)
8
118
0
Order By: Relevance
“…In contrast, downregulation of Cdc42 signals can inhibit anchorage-independent growth and induce apoptosis via the PI(3)K-Akt and Erk signaling cascades and the p53 tumor suppressor (8). Consistent with these reports, Cdc42 silencing by small hairpin RNA was able to reverse the metastatic and growth behavior of human colorectal cancer cells and bladder cancer cells (9,10). Taken together, the observed effects of Cdc42 over-expression and silencing on the cell malignant transformation indicate a role for Cdc42 in regulating tumor metastasis and progression.…”
Section: Introductionsupporting
confidence: 72%
“…In contrast, downregulation of Cdc42 signals can inhibit anchorage-independent growth and induce apoptosis via the PI(3)K-Akt and Erk signaling cascades and the p53 tumor suppressor (8). Consistent with these reports, Cdc42 silencing by small hairpin RNA was able to reverse the metastatic and growth behavior of human colorectal cancer cells and bladder cancer cells (9,10). Taken together, the observed effects of Cdc42 over-expression and silencing on the cell malignant transformation indicate a role for Cdc42 in regulating tumor metastasis and progression.…”
Section: Introductionsupporting
confidence: 72%
“…[19][20][21][22][23][24] We therefore evaluated the expression levels of seven targets of miR-137 (MITF, MIB1, CDK6, CDC42, JARID1B, EZH2 and E2F6 ) and one upstream regulator of miR-137 (MECP2) employing the NimbleGen whole-genome expression array 25 in a subset of the WT and MUT samples (n = 19 and 5, respectively). Two transcript variants were spotted on the array for MECP2 (NM_004992 and NM_001110792) and CDK6 (NM_001259 and NM_001145306).…”
Section: Resultsmentioning
confidence: 99%
“…Actually, some reports have shown that miR-137 has various targets, such as Cdc42, pyruvate kinase isozymes, Formin-like 2, and paxillin, which are related to invasion, the inhibition of the Warburg effect, and metastasis in colorectal cancers, respectively (31)(32)(33)(34). In addition, miR-137 is epigenetically regulated through promoter hypermethylation in colorectal cancers and the epigenetic silencing of miR-137 occurs at the early stage of colorectal carcinogenesis (35).…”
Section: Discussionmentioning
confidence: 99%